Manuel Salazar Zúñiga: His artistic and musical legacy on the fiftieth anniversary of his meritorious honor - Lobo Bejarano, Luis Gustavo (2024)
The interest of this article is to demonstrate the greatness of Manuel (Melico) Salazar (1887-1950), the highest tenor of Costa Rica. He sang in the most famous theaters in the world, along with the best opera singers of his time.